Tracing home address exemptions in state FOI laws - Gil, Jodie (The Journal of Civic Information, 2019)
Privacy concerns have prompted many states to close off once-public information from release through the freedom of information process. This study looks at the personal privacy exemptions for home addresses in 50 states and Washington, D.C., in both 2011 and 2019. There were 16 instances of a change in state law during that time – only three toward more transparency. Voter registration records were the most open of the three categories reviewed, with more than half the states requiring disclosure of home addresses in 2019. This study can help guide journalists, policy makers and records holders as they navigate proposed changes to FOI laws.
Keywords: dept.jrn; peer-reviewed